2022
DOI: 10.1111/hepr.13765
|View full text |Cite
|
Sign up to set email alerts
|

Overestimated renal function in patients with liver cirrhosis predicts poor prognosis

Abstract: Aim: A high prevalence of overestimated renal function in patients with liver cirrhosis (LC) has been reported; nonetheless, its impact on prognosis remains unclear. We aimed to evaluate the impact of overestimated renal function on prognosis in patients with LC.Methods: An overestimated renal function was defined as a >20% increase in the creatinine-based estimated glomerular filtration rate (eGFR), compared with cystatin C-based eGFR. LC patients with conserved serum, who were evaluated for muscle atrophy an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…This could be due to appetite loss, causing deterioration of the liver functional reserve, which in turn hindered salvage therapy after lenvatinib treatment. Additionally, elevated FGF21 [ 35 ] and decreased food intake could cause a loss of muscle mass, as sarcopenia in patients with chronic liver disease [ 36 , 37 , 38 ] is an independent factor that contributes to poor prognosis. It might also affect the poor patient prognosis observed in this study.…”
Section: Discussionmentioning
confidence: 99%
“…This could be due to appetite loss, causing deterioration of the liver functional reserve, which in turn hindered salvage therapy after lenvatinib treatment. Additionally, elevated FGF21 [ 35 ] and decreased food intake could cause a loss of muscle mass, as sarcopenia in patients with chronic liver disease [ 36 , 37 , 38 ] is an independent factor that contributes to poor prognosis. It might also affect the poor patient prognosis observed in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Laboratory data were evaluated, and imaging tests were performed using echocardiography, CT, or MRI to detect HCC occurrence and recurrence. In this study, referring to the previous studies [ 22 , 23 , 24 ], liver cirrhosis was diagnosed by laboratory findings, liver histology, radiologic findings, and/or liver stiffness data using FibroScan (Echosens, Paris, France).…”
Section: Methodsmentioning
confidence: 99%
“…Clinical information was collected from the enrolled patients, which included laboratory data, history or presence of HCC, treatments for HBV infection, HBV status, coinfection with HIV or HCV, and FIB‐4 index. We diagnosed LC using liver biopsy, Fibroscan data; Echosens, radiological findings, and laboratory data as previously described 11,12 …”
Section: Methodsmentioning
confidence: 99%
“…We diagnosed LC using liver biopsy, Fibroscan data; Echosens, radiological findings, and laboratory data as previously described. 11,12 The ethics committee of Hokkaido University Hospital confirmed that the study protocol (IRB 021-0164) conformed to the ethical guidelines of the Declaration of Helsinki. Patients who provided written informed consent or did not decline to participate were included in the study.…”
Section: Included Patients and Study Designmentioning
confidence: 96%